IMPACT OF CORPORATE SOCIAL RESPONSIBILITY, GENERAL ATTITUDE, TRUST AND PERCEIVED CONSUMER EFFECTIVENESS ON PURCHASE INTENTION (CASE OF H&M CUSTOMERS IN JABODETABEK) - Valerie Aurora Gunawan; Innocentius Bernarto (Indonesian Marketing Journal, 2021)
This study aims to analyze the positive influence of corporate social responsibility on purchase intention through trust, general attitude, and perceived consumer effectiveness. The survey method was implemented in this study. Data was collected using a questionnaire instrument. The target population is all customers who have shopped at H&M in the Jabodetabek area. The number of samples is 400 respondents. The sampling technique was done by convenience sampling. Data analysis with Partial least Square-Structural Equation Modeling approach with the help of SmartPLS 3.0 program. The results show that corporate social responsibility has a positive effect on general attitude, trust, and perceived consumer effectiveness. Likewise, general attitude, trust, and perceived consumer effectiveness have a positive effect on purchase intention.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk menganalisis pengaruh positif corporate social responsibility terhadap purchase intention melalui trust, general attitude, dan perceived consumer effectiveness. Metode survei diimplementasikan dalam penelitian ini. Pengumpulan data dilakukan dengan menggunakan instrumen kuesioner. Target populasi adalah semua pelanggan yang pernah berbelanja di H&M wilayah Jabodetabek. Jumlah sampel sebesar 400 responden. Teknik pengambilan sampel dilakukan dengan convenience sampling. Analisis data dengan pendekatan Partial least Square-Structural Equation Modeling dengan bantuan program SmartPLS 3.0. Hasil penelitian menunjukan bahwa corporate social responsibility berpengaruh positif terhadap general attitude, trust, dan perceived consumer effectiveness. Begitu juga, general attitude, trust, dan perceived consumer effectiveness berpengaruh positif terhadap purchase intention.